Building on European scientific excellence to develop an educational program on intermodal connections for Latvia and the region - Mitropoulos, Lambros; Adamos, Giannis; Nathanail, Eftihia; Yatskiv (Jackiva), Irina; Kabashkin, Igor (Transport, 2017)
Economic and social factors, including existing trends in urban population and employment growth combined with urbanization, have led to enhanced consumption and thus, increasing freight flows in the cities. Mitigation of transport impacts has led to plans towards a more sustainable urban environment. However, managerial and regulatory barriers restrict the incorporation of technological instruments and solutions to the sustainable dimension of decision-making and planning. This paper has sought to bridge this gap by organizing an educational and training program, which involves the participation of todays and tomorrow’s researchers, decision-makers and practitioners. Towards this direction, a methodology is developed that identifies existing gaps between the transport industry and the existing research, education and training programs and converts identified requirements and gaps into training courses. The paper addresses the context of intermodal interconnections for the case of Latvia and the region for stimulating and strengthening its scientific and technological capacity by providing knowledge in the field of smart interconnecting sustainable transport networks. The 2-level gap analysis that was developed and implemented with respect to the thematic areas of (1) ‘Governance and policy development’, (2) ‘Smart solutions’, and (3) ‘Decision-making’, and the validation process that followed, has revealed several requirements that exist currently for passenger and freight interchanges and educational programs for Latvia and the region. Based on the identified educational requirements for Latvia and the region, 20 educational areas were created that resulted in 12 courses for passenger and freight transport interchanges that are going to be used for training and education in Latvia.